Intraspecific variations in responses to ocean acidification in two branching coral species. Issue 1 (15th September 2017) - Sekizawa, Ayami; Uechi, Hikaru; Iguchi, Akira; Nakamura, Takashi; Kumagai, Naoki H.; Suzuki, Atsushi; Sakai, Kazuhiko; Nojiri, Yukihiro
Abstract: Ocean acidification is widely recognised to have a negative impact on marine calcifying organisms by reducing calcifications, but controversy remains over whether such organisms could cope with ocean acidification within a range of phenotypic plasticity and/or adapt to future acidifying ocean. We performed a laboratory rearing experiment using clonal fragments of the common branching corals Montipora digitata and Porites cylindrica under control and acidified seawater (lower pH) conditions (approximately 400 and 900 μatm p CO2, respectively) and evaluated the intraspecific variations in their responses to ocean acidification. Intra- and interspecific variations in calcification and photosynthetic efficiency were evident according to both p CO2 conditions and colony, indicating that responses to acidification may be individually variable at the colony level. Our results suggest that some corals may cope with ocean acidification within their present genotypic composition by adaptation through phenotypic plasticity, while others may be placed under selective pressures resulting in population alteration. Highlights: Responses of two branching corals in the acidified seawater were evaluated. Intra- and interspecific variations in calcification and photosynthetic efficiency were evident in acidified seawater. Some corals may cope with future ocean acidification by adaptation and/or phenotypic plasticity.